Reliability of Pressure Waveform Analysis to Determine Correct Epidural Needle Placement in Laboring Women. Issue 2 (June 2018) - Al-Aamri, I.; Derzi, S.H.; Moore, A.; Elgueta, M.F.; Moustafa, M.; Schricker, T.; Tran, D.Q.
Abstract : ( Anaesthesia . 2017;72(7):840–844) Epidural failure is a significant problem in obstetric anaesthesia with one survey of parturients reporting a failure rate of 23%. There can be many causes of epidural failure, including technical failure due to misidentification of the epidural space. A false loss-of-resistance during epidural needle advancement is a common cause of misidentification. Pressure waveform analysis has been used to provide confirmation of correct epidural needle position when the loss-of-resistance technique was used to identify the epidural space during thoracic epidural procedures. Accurate needle placement is confirmed if a pulsatile waveform synchronized with arterial pulsations is seen. In one study, the failure rate decreased from 24% with loss-of-resistance only to 2% with the addition of pressure waveform analysis. However, the reliability of this technique for lumbar epidural analgesia for labor is unclear. This observational study was performed to determine the reliability of pressure waveform analysis in identifying accurate epidural needle placement during lumbar epidural insertion for labor analgesia.